1986
DOI: 10.1366/0003702864508502
|View full text |Cite
|
Sign up to set email alerts
|

A High-Vacuum-Cell Approach to SERS Studies of Thin Films on Nonmetallic Surfaces

Abstract: A high-vacuum cell designed for obtaining surface-enhanced Raman scattering (SERS) spectra of thin films on nonmetallic surfaces is described. The cell is shown to improve one's ability to obtain SERS spectra with acceptable S/N ratios and drastically reduced interference from sample alteration and/or bands typically assigned to graphitic carbon. This cell forms the basis of a pragmatic approach to obtaining SERS spectra from interfacial systems that applied surface scientists will likely be faced with in thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…However, SERS may contribute to an understanding of its thermal decomposition, [26] especially if the metallic SERS substrate does not alter the usual mechanistic pathway by participating chemically in the degradation process. It has been suggested that reactions involving silver catalyze polystyrene degradation during SERS; [26,27] but our SERS substrates, which are composed of unreactive gold, yield no fewer decomposition peaks than SERS substrates composed of silver. [26,27] Thus we provide evidence that silver substrates do not participate, chemically, in the degradation process.…”
Section: Introductionmentioning
confidence: 76%
See 4 more Smart Citations
“…However, SERS may contribute to an understanding of its thermal decomposition, [26] especially if the metallic SERS substrate does not alter the usual mechanistic pathway by participating chemically in the degradation process. It has been suggested that reactions involving silver catalyze polystyrene degradation during SERS; [26,27] but our SERS substrates, which are composed of unreactive gold, yield no fewer decomposition peaks than SERS substrates composed of silver. [26,27] Thus we provide evidence that silver substrates do not participate, chemically, in the degradation process.…”
Section: Introductionmentioning
confidence: 76%
“…It has been suggested that reactions involving silver catalyze polystyrene degradation during SERS; [26,27] but our SERS substrates, which are composed of unreactive gold, yield no fewer decomposition peaks than SERS substrates composed of silver. [26,27] Thus we provide evidence that silver substrates do not participate, chemically, in the degradation process.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations